2012
DOI: 10.1021/la3042742
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Scanning Tunneling Microscopy Investigation of Subphthalocyanine and Subnaphthalocyanine Adlayers on a Au(111) Electrode

Abstract: The adsorption behaviors of subphthalocyanine (SubPc) and subnaphthalocyanine (SubNc) on the Au(111) surface were investigated by electrochemical scanning tunneling microscopy (ECSTM). Two types of ordered adlayer structures of SubPc were observed at 550 mV versus the reversible hydrogen electrode (RHE). All of the SubPc molecules take the Cl-down adsorption configuration on Au(111) in both structures. The ordered adlayers exist in the potential range between 350 and 650 mV. The SubNc molecules adsorb on Au(11… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 51 publications
(75 reference statements)
1
5
0
Order By: Relevance
“…The underlying Au(111) herringbone reconstruction was still discernible after the deposition of Nile Red, as has been reported for the MLs of porphyrins and phthalocyanines adsorbed on Au(111). However, although these studies reported that the corresponding molecular networks formed were characterized by a precise orientation with respect to the gold surface, , here, we found that Nile Red molecular packings did not orient along the six-fold symmetry of Au(111) but oriented randomly with respect to the crystalline substrate. Although a complex interplay can exist between the organization of surface-deposited molecules and the herringbone reconstruction of Au(111), as with the deposition of ZnTPP molecules, in general, the Au(111) herringbone reconstruction can be lifted after the absorption of interacting molecules , or remain unaltered in case of molecular adsorption at the surface .…”
Section: Results and Discussionsupporting
confidence: 80%
“…The underlying Au(111) herringbone reconstruction was still discernible after the deposition of Nile Red, as has been reported for the MLs of porphyrins and phthalocyanines adsorbed on Au(111). However, although these studies reported that the corresponding molecular networks formed were characterized by a precise orientation with respect to the gold surface, , here, we found that Nile Red molecular packings did not orient along the six-fold symmetry of Au(111) but oriented randomly with respect to the crystalline substrate. Although a complex interplay can exist between the organization of surface-deposited molecules and the herringbone reconstruction of Au(111), as with the deposition of ZnTPP molecules, in general, the Au(111) herringbone reconstruction can be lifted after the absorption of interacting molecules , or remain unaltered in case of molecular adsorption at the surface .…”
Section: Results and Discussionsupporting
confidence: 80%
“…SubNc is a larger molecule than SubPc, and it has been shown to have a packing density lower than that of SubPc on Au surfaces. 36 It is also likely that due to the partial chlorination of the SubNc macrocycle, the intrinsic dipole of the molecule is reduced from that of the non-chlorinated molecule.…”
Section: Resultsmentioning
confidence: 99%
“…The dipole moment is expected to be nearly identical for both materials. ,, However, one could anticipate that the collective interface dipole may be lower for SubNc than for SubPc because of a lower interfacial packing density. SubNc is a larger molecule than SubPc, and it has been shown to have a packing density lower than that of SubPc on Au surfaces . It is also likely that due to the partial chlorination of the SubNc macrocycle, the intrinsic dipole of the molecule is reduced from that of the non-chlorinated molecule.…”
Section: Resultsmentioning
confidence: 99%
“…Electrochemical scanning tunneling microscopy (ECSTM) studies have recently provided direct evidence for understanding the potential-controlled adsorption behaviors of SubPc 1 and SubNc 43 on a Au(111) surface. 245 Ordered SubPc monolayers with Cl-down adsorption configuration were observed within the potential window between 350 and 650 mV (vs the reversible hydrogen electrode, RHE). However, out of this window, the SubPc molecules either desorb from the substrate at more negative potentials or adsorb in a disordered form at higher potentials.…”
Section: Organization In Liquid Crystallinementioning
confidence: 99%